Manajemen Operasi Dakwah:Investigasi Eksplanatori pada Program Khutbah Jumat di Masjid Al-Falah Surabaya - Thoha, A. Faiz Khudlari; Gunawan, Reka; Subandi, Bambang (Masjiduna : Junal Ilmiah Stidki Ar-Rahmah, 2019)
This study aims to provide an overview of the strategy and management of the Friday Khutbah production process at the Al-Falah Mosque in Surabaya as its object. The method used by researchers in this research is a case study with data collection procedures using in-depth interviews, observation, and documentation. So that researchers can explore the phenomenon of the object of research in detail and depth. The findings that occur in the field show results that are sharpened by descriptive descriptions of several categories of production. First, the process of determining the idea of the Friday sermon program at Al-Falah Mosque. Second, for the selection mechanism for Friday sermons at Al-Falah Mosque. Third, the design of the Friday sermon program at Al-Falah Mosque. Fourth, testing and evaluating the Friday sermon program at Al-Falah Mosque. Fifth, the final design of the Friday sermon program at Al-Falah Mosque.